Small and Medium Enterprises Growth and Competitiveness: the Importance of Marketing Strategies Role - Hassan Muazu , Muazu; Nashehu, Hauwa'u Hassan; Shehu, Ummi Rahma (Journal of Social Transformation and Regional Development, 2021)
The growing competition among businesses of small medium or large is an area of concern to business growth and competitiveness. Strategies have been used to differentiate the undertakings of various enterprises irrespective of industrial affiliation, specifically marketing strategies are used to reach the customers and tackle competition. The adoption and implementation of unsuitable marketing strategy exposes the weaknesses of small and medium enterprises (SMEs) and the challenges to capture sizable market share. This paper is aimed at examining the types of marketing strategies suitable for SMEs and how they affect their growth and competitiveness in developing countries. A review survey approach was employed in this work and related literature from journal articles, professional reports, term papers and dissertations were reviewed. It has been discovered that marketing strategies like relationship management, branding, product and pricing differentiation, market segmentation and channel cultivation are crucial for the sustainable growth and competitiveness of SMEs in developing countries. Some propositions were made on some unpopular marketing strategies that could be explored by SMEs for competitiveness and international markets.